2007
DOI: 10.1063/1.2789178
|View full text |Cite
|
Sign up to set email alerts
|

Electroforming and resistance-switching mechanism in a magnetite thin film

Abstract: The electroforming and the resistance-switching behaviors in magnetite, Fe3O4, by the application of an appropriate electric field are demonstrated on a lateral device with multiple electrodes. By means of this device, both the location and the nature of the change in Fe3O4 are specified from the electrical measurements and Raman spectroscopy. The switching phenomenon is caused in maghemite, γ-Fe2O3, which is formed by oxidation of Fe3O4, near an interface of an anode. The authors argue that the switching moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 19 publications
2
64
1
Order By: Relevance
“…Despite this promise, answers to some key questions have remained elusive for the devices due to the lack of solid experimental evidence and the metal oxide technology has not yet matured. 1 The least understood, and most problematic, step in the operation of these metal oxide switches is typically the 'electroforming' process, a one-time application of high voltage or current that produces a significant change of electronic conductivity [27][28][29][30]. Subsequent to this change the devices operate as tunable resistance switches, but with a wide variance of properties dependent on the details of the electroforming.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this promise, answers to some key questions have remained elusive for the devices due to the lack of solid experimental evidence and the metal oxide technology has not yet matured. 1 The least understood, and most problematic, step in the operation of these metal oxide switches is typically the 'electroforming' process, a one-time application of high voltage or current that produces a significant change of electronic conductivity [27][28][29][30]. Subsequent to this change the devices operate as tunable resistance switches, but with a wide variance of properties dependent on the details of the electroforming.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Interestingly, Fe 3 O 4 exhibits a highly conducting property while γ-Fe 2 O 3 exhibits an insulating property. [25], [26] In our GF films, the conducting In the low voltage regime of the LRS, the current conduction is ohmic in nature (slope ~1). In the high voltage regime, near the switching voltage, the slope is found to be ~ 1.5.…”
Section: (B) and (C) Respectivelymentioning
confidence: 99%
“…For example, FeO x thin films have been reported to show digital-type unipolar switching through the formation and rupture of conducting filaments 18 and bipolar switching due to redox reaction. 19 On the other hand, the maghemite (c-Fe 2 O 3 ) NPs assembly presented the analog memristive switching with sequentially changing resistance. 16 Also, we have reported that NiO x NPs assembly exhibited both digital-and analog type switching characteristics depending on the thickness, 17 while NiO thin films have been reported to show digital-type unipolar switching.…”
Section: Introductionmentioning
confidence: 99%